2019
DOI: 10.1097/j.pain.0000000000001528
|View full text |Cite
|
Sign up to set email alerts
|

Axon degeneration: mechanistic insights lead to therapeutic opportunities for the prevention and treatment of peripheral neuropathy

Abstract: Peripheral neuropathy is the most common neurodegenerative disease affecting hundreds of millions of patients worldwide and is an important cause of chronic pain. Typical peripheral neuropathies are characterized by dysesthesias including numbness, crawling skin, a sensation of “pins and needles,” and burning and stabbing pain. In addition, peripheral neuropathy can affect the motor and autonomic systems leading to symptoms such as weakness, constipation, and dysregulation of blood pressure. Peripheral neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 78 publications
0
34
0
Order By: Relevance
“…It acts by blocking the activation of wild-type SARM-1, and this protects axons from damage. Gene therapy using AAV-mediated delivery of this SARM-1 dominant-negative molecule provided long-lasting axonal protection [114]. In addition, SARM1-mediated NADH dehydrogenase subunit I (NAD1) destruction and loss is compensated by the development of NAD1 precursors, which have the potential ability to protect axons.…”
Section: Future Outlook: Data From Preclinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It acts by blocking the activation of wild-type SARM-1, and this protects axons from damage. Gene therapy using AAV-mediated delivery of this SARM-1 dominant-negative molecule provided long-lasting axonal protection [114]. In addition, SARM1-mediated NADH dehydrogenase subunit I (NAD1) destruction and loss is compensated by the development of NAD1 precursors, which have the potential ability to protect axons.…”
Section: Future Outlook: Data From Preclinical Studiesmentioning
confidence: 99%
“…In addition, SARM1-mediated NADH dehydrogenase subunit I (NAD1) destruction and loss is compensated by the development of NAD1 precursors, which have the potential ability to protect axons. These NAD1 precursors are natural products that have potential utility in CIPN prevention [114]. In addition to the direct influence on SARM-1, targeting the upstream pathways regulating SARM-1 to prevent CIPN is of interest.…”
Section: Future Outlook: Data From Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of myelin and changes to the axonal cytoskeleton may alter the structure and impair the function of peripheral nerves, thus leading to the development of sensory and motor peripheral neuropathy and altered pain perception. The molecular mechanisms of these phenomena are not fully established [43,63,67].…”
Section: Axonal Degenerationmentioning
confidence: 99%
“…Recent studies have also identified a new molecular mechanism involving sterile alpha and TIR motif-containing protein 1 (SARM1) as an injury-inducible NADase that triggers axonal loss [9,67]. The activation of SARM1 has been shown to contribute to Wallerian degeneration, a phenomenon that occurs during axonal degeneration [72].…”
Section: Axonal Degenerationmentioning
confidence: 99%